A new method to investigate the catalytic mechanism of YhdE pyrophosphatase by using a pyrophosphate fluorescence probe - Qingya Shen (Nature Portfolio, 2017)
Abstract YhdE is a Maf (multicopy associated filamentation) proteins from Escherichia coli which exhibits pyrophosphatase activity towards selected nucleotides, although its catalytic mechanism remains unclear. Herein we used a novel fluorescence probe (4-isoACBA–Zn(II) complex) to characterize the enzymatic properties of YhdE and its mutant, establishing a new method for assaying pyrophosphatase catalytic function. Our results reveal for the first time that the new fluorescence sensor confers high sensitivity and specificity and pyrophosphate (PPi) is the direct catalytic product of YhdE. Crystal structures of a mutant in the active-site loop (YhdE_E33A) show conformational flexibility implicated in the catalytic mechanism of YhdE. ITC experiments and computational docking further reveal that Asp70 and substrate dTTP coordinate Mn2+. Quantum mechanics calculations indicate that YhdE hydrolysis appears to follow a stepwise pathway in which a water molecule first attacks the α-phosphorus atom in the substrate, followed by the release of PPi from the pentavalent intermediate.